If it's not what You are looking for type in the equation solver your own equation and let us solve it.
28(5x-4)=82(2x+8)
We move all terms to the left:
28(5x-4)-(82(2x+8))=0
We multiply parentheses
140x-(82(2x+8))-112=0
We calculate terms in parentheses: -(82(2x+8)), so:We get rid of parentheses
82(2x+8)
We multiply parentheses
164x+656
Back to the equation:
-(164x+656)
140x-164x-656-112=0
We add all the numbers together, and all the variables
-24x-768=0
We move all terms containing x to the left, all other terms to the right
-24x=768
x=768/-24
x=-32
| j−361=360 | | 7f-10=f+3f+8 | | 5x-10=4x+11,x | | 6(b-2)=-5+5b | | c+32=842 | | 5h+4h+12=66 | | (17x+9)=46 | | g+156=287 | | 48-2y=22 | | 70-(5y+3)=22 | | n-0.05=57 | | 32+9y=13y | | 4b+3)+2b=3(b-11 | | 4(v-5)=-8-8v | | 1/2(6x+10)=3x+10 | | –14+4r=2 | | v/5=-3/5 | | 2n+12+3n=n-16 | | x+6+x=6-1(-2x) | | 132+12x=180,x | | 7(1+7a)=7+3a | | 4w+2=–6 | | 1.5x-1.5=2x+6 | | 46+h=287 | | 7(2x+1)=6(3x) | | 5(2x+9)+2(x+11)=3(3x=4)+46# | | 45-5q=6 | | -5+5(-5-5r)=6r+1 | | 6t+18=48 | | 3g-6=-12+g | | 32=w=9w | | 4r-8=-64 |